KONTRIBUSI PROGRAM VOLUNTEER MAHASISWA KE LUAR NEGERI BAGI INTERNASIONALISASI PERGURUAN TINGGI - Syaefudin, Mohamad; Agustiningrum, Tri Eko (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
Volunteer abroad programs for students have many challenges but also contribute to the development of human resources in the future. This paper aims to explain the volunteer program of students to abroad and their contribution to the internationalization of higher education. The study was conducted on four informants who participated in volunteer programs abroad and a NGO of volunteer programs through interview techniques and documentation. The research findings show that student volunteer programs abroad developped the international reputation of a university by seeing (1) the process of becoming a volunteer begins with collaboration between institutions, registration, selection and placement of participants; (2) volunteers conduct work programs in the fields of education and social affairs on an international scale; (3) this program greatly impacts the development of knowledge and social work experience of participants which impacts on career development in professional field; (4) volunteer programs are also an important point in developing university international cooperation.